2019
DOI: 10.1111/jels.12234
|View full text |Cite
|
Sign up to set email alerts
|

Furman at 45: Constitutional Challenges from California's Failure to (Again) Narrow Death Eligibility

Abstract: The Eighth Amendment's "narrowing" requirement for capital punishment eligibility has challenged states since it was recognized in Furman v. Georgia in 1972. This article examines whether California's death penalty scheme complies with this requirement by empirically analyzing 27,453 California convictions for first-degree murder, second-degree murder, and voluntary manslaughter with offense dates between January 1978 and June 2002. Using a 1,900-case sample, we examine whether California's death penalty statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 2 publications
1
18
0
Order By: Relevance
“…The key goal of Furman (1972) and the legislation pursuant to it was to limit discretion and narrow the death penalty to the most serious offenders. We agree with Baldus et al (2019), Barnes et al (2009), Marceau et al (2013), and others that the clearest of these remedies is to strengthen this "narrowing function" that is supposed to be performed by statutory definitions of aggravating factors. Failing to perform that narrowing function permits wide geographic disparity (Baldus et al, 2019;Barnes et al, 2009), and the wide discretion some aggravating factors permit was the grounds for the challenge Arizona's death penalty statute in Hidalgo v. Arizona (2018).…”
Section: Suggestions For Remedying Geographic Arbitrarinesssupporting
confidence: 89%
See 4 more Smart Citations
“…The key goal of Furman (1972) and the legislation pursuant to it was to limit discretion and narrow the death penalty to the most serious offenders. We agree with Baldus et al (2019), Barnes et al (2009), Marceau et al (2013), and others that the clearest of these remedies is to strengthen this "narrowing function" that is supposed to be performed by statutory definitions of aggravating factors. Failing to perform that narrowing function permits wide geographic disparity (Baldus et al, 2019;Barnes et al, 2009), and the wide discretion some aggravating factors permit was the grounds for the challenge Arizona's death penalty statute in Hidalgo v. Arizona (2018).…”
Section: Suggestions For Remedying Geographic Arbitrarinesssupporting
confidence: 89%
“…Justice Stephen Breyer (Justice Ruth Bader Ginsburg concurring), in recent dissents in Glossip v. Gross (2015), Jordan v. Mississippi (1986), and Evans v. Mississippi (2018), decried that the death penalty suffered from arbitrary application, in part as a result of wide geographic disparity in death sentences and their concentration in a comparatively small number of counties nationwide. Prior research has shown that different counties have much different rates of seeking and imposing the death penalty (see reviews by Baldus et al, 2019;Barnes et al, 2009;Gould & Leon, 2017). Critics would see place-based variation in murder case processing and sentencing as an unwarranted disparity that comes close to the kind of arbitrariness that Furman v. Georgia (1972) decried.…”
Section: Geographical Arbitrarinessmentioning
confidence: 99%
See 3 more Smart Citations